Breaking the scaling relationship via thermally stable Pt/Cu single atom alloys for catalytic dehydrogenation. Issue 1 (December 2018) - Sun, Guodong; Zhao, Zhi-Jian; Mu, Rentao; Zha, Shenjun; Li, Lulu; Chen, Sai; Zang, Ketao; Luo, Jun; Li, Zhenglong; Purdy, Stephen; Kropf, A. Jeremy; Miller, Jeffrey; et al.
Abstract Noble-metal alloys are widely used as heterogeneous catalysts. However, due to the existence of scaling properties of adsorption energies on transition metal surfaces, the enhancement of catalytic activity is frequently accompanied by side reactions leading to a reduction in selectivity for the target product. Herein, we describe an approach to breaking the scaling relationship for propane dehydrogenation, an industrially important reaction, by assembling single atom alloys (SAAs), to achieve simultaneous enhancement of propylene selectivity and propane conversion. We synthesize γ-alumina-supported platinum/copper SAA catalysts by incipient wetness co-impregnation method with a high copper to platinum ratio. Single platinum atoms dispersed on copper nanoparticles dramatically enhance the desorption of surface-bounded propylene and prohibit its further dehydrogenation, resulting in high propylene selectivity (~90%). Unlike previous reported SAA applications at low temperatures (<400 °C), Pt/Cu SAA shows excellent stability of more than 120 h of operation under atmospheric pressure at 520 °C. Enhancing the catalytic activity of noble-metal alloys is frequently accompanied by side reactions. Here, the authors describe an approach to break the scaling relationship for propane dehydrogenation, by assembling single atom alloys, to achieve simultaneous enhancement of propylene selectivity and propane conversion.